Effects of water chemistry on the dissolution of ZnO nanoparticles and their toxicity to Escherichia coli - Li, Mei; Lin, Daohui; Zhu, Lizhong (Environmental pollution (1987), 2013)
The dissolution of ZnO nanoparticles (nano-ZnO) plays an important role in the toxicity of nano-ZnO to the aquatic organisms. The effects of water chemistry such as pH, ionic components, and dissolved organic matter (DOM) on the dissolution of nano-ZnO and its toxicity to Escherichia coli (E. coli) were investigated in synthetic and natural water samples. The results showed that the toxicity of nano-ZnO to E. coli depended on not only free Zn2+ but also the coexisting cations which could reduce the toxicity of Zn2+. Increasing solution pH, HPO42−, and DOM reduced the concentration of free Zn2+ released from nano-ZnO, and thus lowered the toxicity of nano-ZnO. In addition, both Ca2+ and Mg2+ dramatically reduced the toxicity of Zn2+ to E. coli. These results highlight the importance of water chemistry on the toxicity evaluation of nano-ZnO in natural waters. ► The effects of water chemistry on the toxicity of nano-ZnO were investigated. ► Increasing solution pH, HPO42−, and DOM reduced nano-ZnO toxicity to E. coli. ► Ca2+ and Mg2+ could dramatically reduce the toxicity of nano-ZnO to E. coli. ► Free Zn2+ ions and water hardness together controlled nano-ZnO toxicity in waters. The toxicity of nano-ZnO to E. coli depended on not only free Zn2+ but also Ca2+ and Mg2+ which could reduce the toxicity of Zn2+.